Impact of climate change on soil health - Benbi, D.K. (Annals of Agricultural Research, 2014)
The increasing concentration of greenhouse gases (GHGs) is bringing about major changes to the global environment resulting in global warming, depletion of ozone concentration in the stratosphere, changes in atmospheric moisture and precipitation and enhanced atmospheric deposition. These changes impact several soil processes, which influence soil health. In this paper, the impact of climate change on soil health especially on soil organic C (SOC) and N dynamics in soil and strategies to improve SOC pool and soil health are discussed. A number of physical, chemical and biological characteristics have been proposed as indicators of soil quality. Soil organic matter (SOM) exerts a major influence on several soil quality indicators and is thus considered a key indicator of soil health. An optimal level of SOM is essential for maintaining soil health and alleviating rising atmospheric CO2 concentration. Management practices or technologies that increase C input to the soil and reduce C emissions or both enhance soil organic C pool. Biological processes in soil such as decomposition of organic matter, C and N cycling, microbial and metabolic quotients are likely to be influenced greatly by climate change. Changes in climate are likely to influence dynamics of SOM, both directly through changes in temperature and water balance and indirectly through changes in primary productivity. Future trend in SOC content will depend on the relative temperature sensitivities of organic matter decomposition and primary production. During the last 150 years atmospheric N depositions have increased greatly and these are projected to increase further by 2.5 times by the year 2100. The deposited N besides impacting a number of processes in soil significantly modifies the global C and N cycles. In view of changing climate, it is imperative to maintain soil health as a healthy soil can sustain its functions and provide ecosystem resilience.